"Citizens but for Papers:" Undocumented Youth Organizations, Anti-Deportation Campaigns, and the Reframing of Citizenship. (28th February 2017) - Patler, Caitlin
Abstract: Scholars have documented strong anti-immigrant bias in mainstream media portrayals and public sentiment, especially associated with notions of "illegality." Yet certain groups of undocumented immigrants have been able to defend their continued residency. How are undocumented immigrants, as marginalized subjects, able to make claims for legal and social recognition? Through an analysis of 125 anti-deportation campaigns led by undocumented youth organizations in the United States, I show how organizations developed a nationally coordinated model using citizenship frames to challenge deportations and build support for pro-immigrant legislation. Citizenship frames are based in legal and normative ideologies of citizenship that underscore acculturation, civic engagement, and humanitarian concerns. The campaigns highlight undocumented immigrants' social integration, deservingness, and practice of citizenship, therefore contesting the boundaries between citizen and noncitizen, and between lawful and unlawful. Though citizenship frames are used across cases, campaign tactics vary: students are portrayed as high-achievers who would suffer greatly if deported, while campaigns for non-students emphasize the detrimental effects of deportation on others. Importantly, citizenship frames are bounded by the government's priorities for immigration enforcement, with potentially negative consequences for those immigrants considered less than model citizens.